(untitled) - Santrock, John W. (Boston, 2006)
Completely revised and featuring a new design, Life-Span Development 8th edition is the most accurate and up to date text available. Applauded by adopters as eloquently written and intelligently presented, this text bears John Santrock's trademark balance of accurate, current content for faculty and effective pedagogy for students. Included in this new edition are the most cutting edge research available and thoroughly integrated coverage of culture, ethnicity and gender. For students, Santrock's student-celebrated pedagogical system has been enhanced to better help students see how the course material fits together. The new edition features extended coverage of aging material, along with thoroughly updated references and enhanced pedagogical features
Keywords: Developmental psychology,Tiến triển tâm lý